Metafeminism and Post-9/11 Writing in Canada and Québec - Carrière, Marie (Studies in Canadian Literature / Études en littérature canadienne, 2016)
This article considers the impact of crisis in the post-9/11 writing of Nicole Brossard and Margaret Atwood, undeniable trailblazers of literary feminism in Canada. The post-9/11 world newly situates local and global, as well as social and economic challenges that feminism has always confronted. Atwood’s and Brossard’s post-millennial work, particularly its post 9/11 backdrop, widens the scope of feminist social and ethical concerns, as well as the different, expansive outlook of feminist writing in Canada today. Atwood and Brossard have recently set themes and scenes of impending, real, and perceived terrorist and bioterrorist threat, ecological and economic doom, corporate domination, torture, heightened surveillance, and state control in the face of global menace and the framework of vulnerable times. The forty-year span of these two writers’ oeuvre is particularly remarkable. It attests to the very trajectories of Western feminism in Canadian and Québécois literatures, and its culmination in the phenomenon and ethos this article proposes to call metafeminism – that which both transgresses and harks back to familiar feminist positions that continue to impact women’s writing in Canada to this day.